O lugar e o funcionamento do título pela obra de Mattoso Câmara - Dias, Juciele Pereira (2009)
Our research has as objective to propose that book titles which carry linguistic knowledges are mobilized as devices of reflection concerning the archive reading. The proposal is developed according to the perspectives theoretical-methodological of History of Linguistic Ideas (HIL) in relation with Discourse Analysis (AD), as developed by Eni Orlandi, in Brazil. In order to do this, we consider Brazilian history of Linguistics focusing on works of Joaquim Mattoso Câmara Jr. as well as on facts and events that constitute the trajectory of this subject of knowledge. Considering the set of publications of this linguist, we noticed that two manuals and one Dictionary - Elementos de Portuguez (1935) and Princípios de Lingüística Geral: Como fundamento para os Estudos Superiores da Língua Portuguesa (1941), and Dicionário de Fatos Gramaticais (1956) - had been re-titled when reedited. Regarding this, we took as object of study the movement of designations - silenced or imposed - in the re-titled. Thus, the analysis of the mentioned titles, based on HIL/AD, leads us to consider the title as a place that has a singular functioning in works of an author because it is not a closed text. The title is open to the exteriority, to the production conditions, to the academic and life history, to the facts and events that constitute a subject of knowledge.